THE PATTERN OF COMPLEMENTARY FEEDING AFFECTS THE INCIDENCE OF DIARRHEA IN INFANTS - Agestika, Revina (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: Complementary foods for breast milk are foods or drinks that have energy and nutrients that are given to infants or children aged 6-24 months to meet nutritional needs not only from breast milk. One of the causes of diarrhea in toddlers is hygiene, including knowledge and attitudes of mothers in feeding, where babies have been fed other than breast milk before the age of 6 months. The pattern of giving complementary foods to breast milk affects the incidence of diarrhea. According to WHO, infants who receive complementary feeding before the age of six months will have a 17 times greater risk of experiencing diarrhea and 3 times more likely to develop upper respiratory tract infections (ARI) than infants who only receive exclusive breastfeeding and receive complementary feeding on time. The purpose of this study was to determine the relationship between complementary feeding and the incidence of diarrhea in infants by using a literature review study. Methods: This study uses a systematic review of articles published between 2014-2020 in the Science Direct, Scopus, Pubmed, and Google Scholar databases so that the results are 11 articles that are reviewed and meet the inclusion and exclusion criteria, included as samples for further review. Results: The factors that cause diarrhea are the child’s age (6-11 months), the nutritional status of the child, exclusive breastfeeding, bottle feeding, washing hands with water, water supply, use of healthy latrines, and season. Conclusion: there is a relationship between complementary feeding and the incidence of diarrhea in infants. Keywords: Complementary Foods for Breastfeeding, Diarrhea, Infants, Literature Review